The T-loop in details - Amanda Frizzo Viecilli; Maria Perpétua Mota Freitas (Dental Press Journal of Orthodontics)
ABSTRACT Introduction: The T-loop as designed by Burstone is a space closure spring used in the rational application of orthodontic biomechanics. Despite the diversity of studies, there is still no consensus on the optimal parametric characteristics for its conformation. Objective: This study aimed at reviewing the literature on the force systems released by different conformations of the T-loop, according to the type of anchorage and the main characteristics and factors that influence them. Results: Comparing the studies, the need for standardization was perceived in the methodology to shape the loops, regarding the variables that influence the force system. Most of the experimental studies with this loop do not report the vertical movement, nor the steps and angles that occur in the brackets. Clinical studies have obtained more variable results in relation to vertical acting forces, considering the influence of chewing. Conclusion: There is great potential for future studies with this type of loop, especially using nickel-titanium alloys, in order to achieve a pure translational movement without friction, with optimal and constant levels of force.